The pyrrolizidine alkaloids of Senecio chrysocoma and Senecio paniculatus - Logie, Catherine Gwynedd (Rhodes University, Faculty of Science, Department of Chemistry, 1996)
In order to compare the pyrrolizidine alkaloid content of two closely related species, Senecio chrysocoma and S. paniculatus, nine populations of plants distributed between the two species, were examined. Three novel pyrrolizidine alkaloids, 7ÃŸ-angelyl-l-methylene-8âˆ -pyrrolizidine, 7ÃŸ-angelyl-l-methylene-8âˆ -pyrrolizidine and 7ÃŸ-angelyl-l-methyleneSO!-pyrrolizidine-4-oxide, as well as eight known pyrrolizidine alkaloids, 7-angelylhastanecine, 9-angelylhastanecine, 7-angelylplatynecine, 9-angelylplatynecine, 9-angelylplatynecine-4-oxide, sarracine, neosarracine and retrorsine, were isolated and identified by NMR and GC-MS techniques. Traces of five tiglyl isomers, 9-tiglylplatynecine, 9-tigl ylplatynecine-4-oxide, 7ÃŸ-tiglyl-l-methylene-8âˆ -pyrrolizidine, sarranicine and neosarranicine, were also isolated and tentatively identified; however, these compounds could have been artefacts of the extraction and analytical procedures. While both species of plant investigated, S. chrysocoma and S. paniculatus, were found to be morphologically different, their pyrrolizidine alkaloid content was, in fact, very similar. The presence of retrorsine in S. paniculatus plant extracts, but not in those from S. chrysocoma plants, was the only major chemical difference observed. It is perhaps significant that retrorsine was the only macrocyclic pyrrolizidine to be identified. A comprehensive, computerised database of physical data for pyrrolizidine alkaloids has been compiled, which has facilitated the identification of new pyrrolizidines and the examination of trends in proton and carbon-13 NMR data for pyrrolizidine alkaloids. A stereospecific synthesis of 7ÃŸ-angelyl-l-methylene-8âˆ -pyrrolizidine was undertaken toconfirm the absolute stereochemistry of the product isolated from S. chrysocoma and S. paniculatus. An inseparable 5:2 mixture of 7ÃŸ-angelyl-l-methylene-8âˆ -pyrrolizidine and 7ÃŸ-angelyl-l,2-didehydro-l-methyl-8âˆ -pyrrolizidine, together with a small amount of tiglyl isomer, was finally synthesised. The application of various chiral differentiating chromatographic and spectroscopic techniques confirmed that both the natural and synthetic products had the same stereochemistry, permitting the natural alkaloid to be identified as 7ÃŸ-angelyl-methylene-8âˆ -pyrrol izidine
Keywords: Senecio -- Analysis; Pyrrolizidines; Botanical chemistry